GOVERNMENT SCHEMES AND LEGAL PROVISIONS FOR HOMELESS PEOPLE - Kumar, Pradeep; Singh, Manoj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Both national and international laws help homeless people in solving housing problems and human rights problems of homeless people. At the international level, the right to housing of homeless people is enshrined in the economic, social and cultural treaties of homeless people. At the national level, Indian law, especially Article 21, protects the right to life and personal liberty. Under this fundamental right, the Universal Declaration of Human Rights recognizes human dignity and includes the right to a dignified life including housing. The right to dignified housing for homeless people is also included in this. The decision of the Indian Supreme Court is also important in this regard. The following international laws are important for the protection of the rights of homeless people: 1. Universal Declaration of Human Rights 2. International Treaty on Economic, Social and Cultural Rights. The right to dignity including housing of these homeless people has been recognized in this treaty and various states have been encouraged to take the required and positive steps in relation to these homeless people.